PENCEGAHAN TIGA DOSA BESAR DAN STRATEGI PEMBINAAN SISWA KESULITAN BELAJAR DI SDN 1 TOMPOH KABUPATEN TOLITOLI - Silviana Douw; Trisagita Trisagita; Florentina Ndeya; Triagung Lihawa; Randi Ladoka; Afifah Istiqomah (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
This community service program aims to implement the prevention of the three major sins (intolerance, sexual violence, and bullying) and a strategy for mentoring students with learning difficulties at SDN 1 Tompoh. The program was implemented through three main stages: socialization of the prevention of the three major sins to teachers, students, and parents; intensive guidance for students experiencing reading difficulties; and observation and evaluation of program implementation. The program results showed that the socialization raised awareness throughout the school community about the importance of preventing the three major sins in the educational environment. The reading guidance program positively impacted improving student literacy skills, while observations identified positive behavioral changes in both students and support from teachers and parents. In conclusion, implementing the prevention of the three major sins and a strategy for mentoring students with learning difficulties at SDN 1 Tompoh has proven effective in creating a safe, inclusive school environment and supporting students' academic development. This program is expected to be implemented sustainably with collaborative support from all relevant parties.